Aguirre, Carlos and Paulo Drinot. The Peculiar Revolution: Rethinking the Peruvian Experiment Under Military Rule. Austin: University of Texas Press, 2017. (5th January 2019) - Willis, Daniel
Abstract : Review of 'The Peculiar Revolution: Rethinking the Peruvian Experiment under Military Rule' by Aguirre, Carlos and Paulo Drinot.